Primary Thyroid Lymphoma: two different presentations of a rare disease - Azlin I,; Leong CF,; NH Hamidah,; Sharifah NA,; Rohaizak M, (Penerbit UKM, 2010)
Primary thyroid lymphoma is a rare disorder accounting for about 2% of all malignant lymphomas and less than 5% of thyroid malignancies. It is an aggressive disease with poor outcome. The majority of thyroid lymphomas are non-Hodgkin lymphomas of Bcell origin. Majority of cases occur in women in the sixth decade. We report two cases of primary thyroid lymphoma and highlight the clinical issues and challenges posed by this rare disease. Both cases presented with respiratory obstructive symptoms that required surgical intervention. The optimal management for a primary thyroid lymphoma be it chemotherapy, radiotherapy, surgery or monoclonal antibodies is still debatable. The role for surgery has evolved through the years but its importance in emergency situations should not be overlooked. Both our patients had to undergo surgery but only one patient received additional chemotherapy and radiotherapy. These two case reports illustrated the difficulties in managing this rare disorder.